PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA KARTU U-MATH (UNO MATHEMATICS) - Savira Fatima Utami; Leonard Leonard (Research and Development Journal of Education, 2023)
The purpose of this research is to develop the design of mathematics learning in grade V elementary school. The design of the learning is expected to facilitate mathematics learning for grade V students. The steps used are ADDIE (Analyze, Design, Development, Implementation, Evaluate). After going through these steps, a learning media in the form of an Uno Mathematics card game was formed. The development of U-MATH (Uno Mathematics) card game media is a modification of the Uno card game. U-MATH card game media is one of the developments of visual-based print media because the media produced through the printing process produces text, graphics, and photos or images displayed on the card. The media consists of 5 chapters consisting of Integer Counting Operations, Fractions, Unit of Measurement, Flat Build, and Simple Space Build. With this teaching material that has been made, it is expected to facilitate students in the process of learning mathematics. In addition, it is able to assist teachers in achieving math learning objective.